Software Quality. Increasing Value in Software and Systems Development 5th International Conference, SWQD 2013, Vienna, Austria, January 15-17, 2013. Proceedings - Winkler, Dietmar.; Biffl, Stefan.; Bergsmann, Johannes. (Lecture Notes in Business Information Processing, 2013)
This book constitutes the refereed proceedings of the 5th Software Quality Days Conference (SWQD) held in Vienna, Austria, in January 2013. This professional symposium and conference offers a range of comprehensive and valuable opportunities for advanced professional training, new ideas, and networking with a series of keynote speeches, professional lectures, exhibits, and tutorials. The seven scientific full papers accepted for SWQD were each peer-reviewed by three or more reviewers and selected out of 18 high-quality submissions. Further, two keynotes and six short papers on promising research directions were also presented and included in order to spark discussions between researchers and practitioners. The papers are organized into topical sections on risk management; software and systems testing; test processes; model-based development; and process improvement and measurement.